Yin and Yang of NADPH Oxidases in Myocardial Ischemia-Reperfusion - Shouji Matsushima; Junichi Sadoshima (MDPI AG, 2022)
Oxidative stress is critically involved in the pathophysiology of myocardial ischemic-reperfusion (I/R) injury. NADPH oxidase (Nox) 2 and 4, major sources of reactive oxygen species (ROS) in cardiomyocytes, are upregulated in response to I/R. Suppression of Nox-derived ROS prevents mitochondrial dysfunction and endoplasmic reticulum (ER) stress, leading to attenuation of myocardial I/R injury. However, minimal levels of ROS by either Nox2 or Nox4 are required for energy metabolism during I/R in the heart, preserving hypoxia-inducible factor-1α (HIF-1α) and peroxisome proliferator-activated receptor-α (PPARα) levels. Furthermore, extreme suppression of Nox activity induces reductive stress, leading to paradoxical increases in ROS levels. Nox4 has distinct roles in organelles such as mitochondria, ER, and ER-mitochondria contact sites (MAMs). Mitochondrial Nox4 exerts a detrimental effect, causing ROS-induced mitochondrial dysfunction during I/R, whereas Nox4 in the ER and MAMs is potentially protective against I/R injury through regulation of autophagy and MAM function, respectively. Although Nox isoforms are potential therapeutic targets for I/R injury, to maximize the effect of intervention, it is likely important to optimize the ROS level and selectively inhibit Nox4 in mitochondria. Here, we discuss the 'Yin and Yang' functions of Nox isoforms during myocardial I/R.